Dietary patterns, overweight and abdominal obesity in people living with HIV/AIDS (Revista Contexto & Saúde, 2026)
Objective To evaluate the association between overweight, abdominal obesity, and dietary patterns in people with HIV/AIDS using antiretroviral therapy. Method: Cross-sectional study with 217 HIV-positive individuals attended at a reference institute for infectious diseases in Teresina, Piauí, Northeast Brazil. Overweight was assessed by body mass index (BMI) and abdominal obesity by waist circumference (WC) and neck circumference (NC). Food consumption was investigated through a 24-hour recall and dietary patterns were identified by the Principal Component Factor Analysis (PCFA) method. The adequacy of PCFA data was verified by the Kaiser-Meyer-Olkin (KMO) test and Bartlett's sphericity test. Poisson regression analysis with robust variance was used to verify the association between variables. Results: Four patterns were identified of dietary patterns, which were monotonous and not very diverse: “Breakfast”, “Traditional”, “Western” and “Healthy” (KMO = 0.5157), poor in food variety. In the adjusted analysis, overweight and abdominal obesity were not associated with the different dietary patterns identified (p 0.05). Conclusion: It was concluded that the dietary pattern in people with HIV/AIDS is not associated with abdominal fat deposition. Food education measures should be intensified for this population, encouraging the consumption of foods rich in immunomodulatory nutrients and improving quality of life.